2021
DOI: 10.3390/md19060327
|View full text |Cite
|
Sign up to set email alerts
|

Malabaricane and Isomalabaricane Triterpenoids, Including Their Glycoconjugated Forms

Abstract: In this review, we discuss structural diversity, taxonomic distribution, biological activities, biogenesis, and synthesis of a rare group of terpenoids, the so-called malabaricane and isomalabaricane triterpenoids, as well as some compounds derived from them. Representatives of these groups were found in some higher and lower terrestrial plants, as well as in some fungi, and in a relatively small group of marine sponges. The skeletal systems of malabaricanes and isomalabaricanes are similar to each other, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 86 publications
0
36
0
Order By: Relevance
“…In addition, saturation of the δ-lactone moiety affects the activity coverage of cell lines, for example, unsaturated 17 showed cytotoxic activities against U-87 (R132H) and U-87 cell lines, but partially saturated 20 did not, although they both exhibited significantly potent activities against HL-60 (FLT3-WT), MV-4-11 (FLT3-ITD mutant), and HCT116 (p53-WT) cell lines (Table S4). Moreover, the geometry of the C-13/C-14 double bond, which could probably be photoisomerized to a mixture of isomers, influences the potencies of both cytotoxicity and antibacterial activities. Such as 17 (13 Z isomer) has more potent cytotoxic activity than 18 (13 E isomer) against all tested cancer cell lines, 2 (13 E ) showed more potent activity against S. aureus than 13 (13 Z ), and geometric isomers 1 , 10 - 12 , exhibited antibacterial activities as follows: 10 (13 E , 23 E ) > 12 (13 E , 23 Z ) > 11 (13 Z , 23 E ) > 1 (13 Z , 23 Z ) against S. pyogenes , and 10 (13 E , 23 E ) > 12 (13 E , 23 Z ) ≈ 11 (13 Z , 23 E ) ≈ 1 (13 Z , 23 Z ) against S. aureus (Tables S4 and S5).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, saturation of the δ-lactone moiety affects the activity coverage of cell lines, for example, unsaturated 17 showed cytotoxic activities against U-87 (R132H) and U-87 cell lines, but partially saturated 20 did not, although they both exhibited significantly potent activities against HL-60 (FLT3-WT), MV-4-11 (FLT3-ITD mutant), and HCT116 (p53-WT) cell lines (Table S4). Moreover, the geometry of the C-13/C-14 double bond, which could probably be photoisomerized to a mixture of isomers, influences the potencies of both cytotoxicity and antibacterial activities. Such as 17 (13 Z isomer) has more potent cytotoxic activity than 18 (13 E isomer) against all tested cancer cell lines, 2 (13 E ) showed more potent activity against S. aureus than 13 (13 Z ), and geometric isomers 1 , 10 - 12 , exhibited antibacterial activities as follows: 10 (13 E , 23 E ) > 12 (13 E , 23 Z ) > 11 (13 Z , 23 E ) > 1 (13 Z , 23 Z ) against S. pyogenes , and 10 (13 E , 23 E ) > 12 (13 E , 23 Z ) ≈ 11 (13 Z , 23 E ) ≈ 1 (13 Z , 23 Z ) against S. aureus (Tables S4 and S5).…”
Section: Resultsmentioning
confidence: 99%
“…6,7,[10][11][12][13][14][15][16][17][18] It has been shown that chemical structures of isomalabaricanes mostly differ at the side chain by the oxidative degeneration, cyclization, and isomerization of double bonds. 3 In the present work, continuing investigation on chemical constituents of R. globostellata, we describe herein the isolation and determination of three new isomalabaricanes (1)(2)(3), a new a-pyrone derivative (4), together with four known isomalabaricane analogs (5-8) (Fig. 1).…”
Section: Introductionmentioning
confidence: 95%
“…These types of compounds display unique chemical structures with a trans-syn-trans 6/6/5 tricyclic nucleus and a polyunsaturated side chain. 3 Additionally, a series of isomalabaricanes exhibited extremely high cytotoxic activity against various cancer cell lines with IC 50 values in the range of nanomolar concentrations. [4][5][6][7] Of these, rhabdastrellic acid A, stelletin A, and stelletin E have been accomplished through total syntheses, providing materials for studying biological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ITTs are tricyclic terpenoids discovered in marine sponges by Ravi et al (1981) [ 9 ]. Forty years later, dozens of studies have contributed to enrich this unique large family of sponge compounds, with more than 160 different structures, usually subdivided into three groups: stellettins (mainly with δ-lactone ring or carboxyl in side chain), stelliferins (oxygenated side chains) and globostellatic acids (carboxylation at C-4) ( Figure 1 ), many of which have significant cytotoxic activities [ 10 , 11 ]. For example, stellettin B ( Figure 1 ) is one of those promising compounds with high antitumor activities [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%